2014
DOI: 10.5539/mas.v8n6p103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Analysis of Dietary Essential Mineral Micronutrients in Selected Malaysian Foods Using FAAS and ICP-MS

Abstract: Food source could provide essential mineral elements necessary for preventing and remedying the cases of Mineral Deficiency Diseases (MDD). This source is cost effective, safe, affordable and accessible. In this study, essential elements: Ca, Mg, P, K, Na, Cu, Fe, Mn, Se and Zn were determined in 126 food samples eaten in Johor Bahru, Malaysia. The all-serving-units-inclusive food samples were oven-dried until constant weight, homogenized and wet digested serially with nitric acid and hydrogen peroxide mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For example, nasi lemak is a dish that specifically cooked in coconut milk and eaten in combination with a gravy, slices of boiled eggs and cucumbers, peanuts and fried anchovies. The similar term was also used to describe this type of food in other studies (Sandra et al, 2012;Salau & Hasan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, nasi lemak is a dish that specifically cooked in coconut milk and eaten in combination with a gravy, slices of boiled eggs and cucumbers, peanuts and fried anchovies. The similar term was also used to describe this type of food in other studies (Sandra et al, 2012;Salau & Hasan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] Salau and Hasan, 2014, have studied major and trace elements in rasam and reported that rasam can be exploited for health maintenance, remedy, and even cure for mineral deficiency diseases. [ 33 ]…”
Section: Role Of Siddha System Of Medicine In South Indian Traditionamentioning
confidence: 99%